Satu Suara untuk Perubahan: Sebuah Projek untuk Mengajak Peserta Didik Menjadi Warganegara yang Baik dan Cerdas - Chania Dwi Chusnul Analisah; Ana Agustin Purwaningsih (Citra Dharma Cindekia, 2023)
The conflicts regarding election results, decreasing public participation in political activities, eroding critical thinking, misinterpretation of freedom of speech, uncontrollable feelings of insecurity due to a lack of self-confidence in facing competition, stereotypes and cynicism corroding respect for diversity and differences are evidence that society has not fully realized its potential. The community has not been able to internalize the noble values of respecting differences, equality, freedom, ethics, and consensus contained in Pancasila. This phenomenon raises the question of how to teach these values to children. What kind of school can accommodate various needs to teach these values? What kind of education is needed? Should education involve more philosophical elements? More media literacy? More elements of citizenship? Or more historical elements? This research aims to describe the implementation of the Strengthening Student Pancasila Profile (P5) project with the theme